Lung clearance of 99mTc-DTPA in systemic lupus erythematosus - Dalcin,P.T.R. (2002)
The early demonstration of lung involvement in systemic lupus erythematosus (SLE) patients is a difficult but important task. In the present study we attempted to identify abnormalities in pulmonary clearance of 99mTc-DTPA in SLE, correlating their clearance data with clinical findings and disease activity. Forty-six consecutive SLE patients with and without active disease (LACC score) and 30 normal volunteers were studied. All subjects were submitted to pulmonary scintigraphy with 99mTc-DTPA to evaluate the pulmonary clearance, and to a chest X-ray, and SLE patients were submitted to tests of disease activity, spirometry, arterial blood gases and tests to assess acute-phase proteins. Pulmonary clearance was faster in SLE patients with active disease when compared to normal controls [half-life of 67.04 min (51.52-82.55 min) in active SLE versus 85.87 min (78.85-92.87 min) in controls, P<0.05] and there was a higher frequency of abnormal clearance rates in patients with active disease (11 of 26 patients, 42.3%) when compared with SLE patients without disease activity (2 of 20 patients, 10%) (P = 0.04). A significant correlation was observed between the clearance rates and cough (P<0.05), but not between the clearance rates and dyspnea symptoms or radiological findings, duration of SLE disease, antinuclear antibody titers and patterns, C-reactive protein or anti-double stranded DNA antibodies. We conclude that the pulmonary clearance of 99mTc-DTPA is increased in SLE patients with active disease.